Analysis of the need for learning media for children with a certainty - Heriani Thamrin; Sunardi Sunardi; Supriyadi Supriyadi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Scholarly communication for children with special needs is significantly different from children in general. The low potential of children with special needs means that their lives differ from those with average abilities. In the aspect of developing the concept of thinking as a whole, it cannot be mastered properly because the IQ level is below the aim of this study to provide opportunities for children with special needs in the aspect of equal rights as children of the nation to get proper education in SLB by developing their potential and interest in themselves. The research methodology uses a descriptive qualitative approach to the literature study design by analysing several references from online journals and ebooks. The study's results describe the role of learning media in increasing the understanding of children with special needs by facilitating two-way communication. Education with feedback transfer of knowledge helps children with special needs optimize growth and development through appropriate talents and interests. Learning media includes the existence of effective media to help children with special needs in optimizing the development of talents and interests and establishing communication by involving teaching aids so that children's talents can develop optimally.